2020
DOI: 10.4081/idr.2020.8748
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy Transmission in Endemic and Non-Endemic Areas Based on the Profile of Antibody Response of PGL-1 and PCR Detection of Mycobacterium leprae DNA from Nasal Swab among Healthy Children of East Java, Indonesia

Abstract: Background: East Java has become one of the provinces that have higher prevalence of leprosy, especially in the coastal region. Environment has also influenced for leprosy transmission and early detection could reduce the incidence rate of new leprosy cases. Epidemiological studies of leprosy in children can give an illustration of the important aspects of the environment. Presence of Mycobacterium leprae (M. leprae) DNA in nasal swabs and seropositivity level among them can describe M. leprae exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Of note was that seroprevalence and incidence rates as well as their correlation remained stable over a period of three years. In 2020, an Indonesian study reported seropositivity of 8.3% in Pacitan (considered a non-endemic district) compared to 48% in Lamongan (considered an endemic district) [76]. Thus, these studies convincingly show the relation between the overall disease incidence in an area and the seroprevalence among PLOS NEGLECTED TROPICAL DISEASES children.…”
Section: The Effect Of Type Of Test On Seroprevalencementioning
confidence: 78%
See 2 more Smart Citations
“…Of note was that seroprevalence and incidence rates as well as their correlation remained stable over a period of three years. In 2020, an Indonesian study reported seropositivity of 8.3% in Pacitan (considered a non-endemic district) compared to 48% in Lamongan (considered an endemic district) [76]. Thus, these studies convincingly show the relation between the overall disease incidence in an area and the seroprevalence among PLOS NEGLECTED TROPICAL DISEASES children.…”
Section: The Effect Of Type Of Test On Seroprevalencementioning
confidence: 78%
“…Most of the seropositive children were not known to have any contact history with leprosy patients and the authors suggested that infection may have originated from unidentified "back-log cases", from non-human M. leprae sources in the environment or from travelling to surrounding areas. A recent paper from 2020 analyzed the presence of M. leprae in nasal swabs and seropositivity levels among 530 elementary schoolchildren from the northern and southern coast of East Java [76]. In Pacitan, an area considered non-endemic for leprosy, 25 out of 301 children (8.3%) were seropositive and in Lamongan, an area considered endemic for leprosy, seropositivity was 48% (110 out of 229).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, epidemiological studies of leprosy in children can point out the important aspects of the environment that influence the leprosy transmission in an endemic area; because children have lower mobility than adults (Adriaty et al, 2020). Evidence also suggests that the degree of vulnerability of the individual, the extent of exposure, and associated environmental factors could potentially influence the transmission.…”
Section: Original Researchmentioning
confidence: 99%
“…The younger patients (<15 years) show active circulation and transmission of Mycobacterium leprae (M. leprae) within the community, thus reflecting inefficiency in the national health system (3)(4)(5). With regard to leprosy in children, the most important matter is the prevention of disability and deformities by early detection and improved treatment of leprosy in leprosy endemic areas (6). Leprosy in children, particularly subclinical leprosy, may occur as currently, treatments are focused only on clinical leprosy, and subclinical leprosy is not a focus, even though patients with subclinical leprosy are sources of further infection.…”
Section: Introductionmentioning
confidence: 99%